Moses Finley and politics - Harris, William V. (William Vernon) (Columbia studies in the classical tradition, 2013)
Marking the centenary of the birth of M.I. Finley, the famous historian of the ancient world and a refugee from McCarthyism, a combined group of ancient and American historians here set out to analyse his political and intellectual evolution.